Ambivalent gender deconstructions reflected through conversations in EFL textbooks for eleventh grade of Indonesian senior high school - Suwastini, Ni Komang Arie; Mihira, Luh Shanti Nilayam; Artini, Ni Nyoman; Jayantini, I Gusti Agung Sri Rwa; Kultsum, Ummi (Universitas Muhammadiyah Sidoarjo, 2026)
Although efforts have been made to reduce gender bias in textbooks, Indonesian English textbooks still tend to reproduce gender-biased oppositions that support patriarchal values. This study aims to analyze how patriarchal values are deconstructed in conversational texts. The research subject was the Indonesian English textbook for the eleventh grade published by the Ministry of Education in 2017, which contains eight chapters and twenty-one conversations. Through McKee's model of textual analysis, this study reveals that the textbook shows a balanced frequency between male and female characters in giving opinions and asking for decisions, with females slightly dominating decision-making. Female characters asked for suggestions more frequently, while males slightly dominated in giving suggestions and more significantly in giving answers. Agreement was more common among females, while males dominated disagreement. While female characters were positioned as decision-makers, this was undermined by the high frequency of male disagreement. The study reveals ambivalence in the deconstruction of male dominance, indicating that stronger efforts are needed to promote gender equality through textbook content.